2018
DOI: 10.3390/jcm7020019
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Transfusion Need for Elective Primary Posterior Lumbar Fusion in A High-Volume Center for Spine Surgery

Abstract: (1) Background: This study evaluated the perioperative red blood cell (RBC) transfusion need and determined predictors for transfusion in patients undergoing elective primary lumbar posterior spine fusion in a high-volume center for spine surgery. (2) Methods: Data from all patients undergoing spine surgery between 1 January 2014 and 31 December 2016 were reviewed. Patients’ demographics and comorbidities, perioperative laboratory results, and operative time were analyzed in relation to RBC transfusion. Multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 43 publications
(85 reference statements)
2
17
0
Order By: Relevance
“…Eight studies demonstrated the association of preoperative anemia with postoperative outcomes following PLF. [15][16][17][18][19][20][21][22] Four studies reported that low preoperative Hb/Hct was associated with increased risk of blood transfusion postoperatively(Table 4). 15,17,18,20 Two studies reported that low preoperative Hb was associated with increased LOS ( Table 5).…”
Section: Plfmentioning
confidence: 99%
“…Eight studies demonstrated the association of preoperative anemia with postoperative outcomes following PLF. [15][16][17][18][19][20][21][22] Four studies reported that low preoperative Hb/Hct was associated with increased risk of blood transfusion postoperatively(Table 4). 15,17,18,20 Two studies reported that low preoperative Hb was associated with increased LOS ( Table 5).…”
Section: Plfmentioning
confidence: 99%
“…Over the past few decades, the number of spinal procedures performed in the United States has increased dramatically, with growth exceeding 200% since the 1990s. [1][2][3][4] As the volume and complexity of spinal procedures rise, intraoperative blood loss management has become a pivotal topic of research within the field. [5][6][7] Many spinal procedures are associated with substantial blood loss.…”
Section: Introductionmentioning
confidence: 99%
“…Beside surgery-related factors, patient-specific characteristics, i.e. age, gender, comorbidities, pre-surgical hemoglobin level, have been associated with perioperative transfusion need [ 4 ]. Accordingly, these factors were not considered in this investigation since they have been already exhaustively described and indeed previously confirmed in our population of lumbar spine fusions [ 1 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…age, gender, comorbidities, pre-surgical hemoglobin level, have been associated with perioperative transfusion need [ 4 ]. Accordingly, these factors were not considered in this investigation since they have been already exhaustively described and indeed previously confirmed in our population of lumbar spine fusions [ 1 , 4 ]. It has been reported that factors associated with perioperative blood transfusion were older age, female gender, higher ASA grade, presence of diabetes, use of anticoagulant/platelet drugs, longer operative time, and low pre-surgery HB levels [ 4 7 ].…”
Section: Discussionmentioning
confidence: 99%